2006
DOI: 10.2143/itl.151.0.2015221
|View full text |Cite
|
Sign up to set email alerts
|

Jordanian EFL Teachers' Perceptions of the Appropriateness of Action Pack Textbooks

Abstract: This study investigates the appropriateness of the Action Pack Textbook Series (APTS) currently taught in the first four primary stage classes in Jordanian public schools. An evaluation checklist, compiled from the literature, and a semi-structured interview were used to evaluate the content, layout, assessment tasks, teacher's book and the availability of supplementary materials. The findings support the following conclusions: Poor ratings were minimal; APTS is adaptable to the needs of bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 5 publications
1
4
0
Order By: Relevance
“…The findings of this study are consistent with the claims of Brown (2001) who confirmed that materials and tasks should be carefully designed to suit the students' level, interests and environment. Along the same lines, Al-Barakat, Bataineh, Al-Karasneh and Bataineh (2006) pointed out that Action Pack through the first to the fourth grade are appropriate to the needs and levels of the students which is also consistent with the findings of this study.…”
Section: Findings and Discussionsupporting
confidence: 90%
“…The findings of this study are consistent with the claims of Brown (2001) who confirmed that materials and tasks should be carefully designed to suit the students' level, interests and environment. Along the same lines, Al-Barakat, Bataineh, Al-Karasneh and Bataineh (2006) pointed out that Action Pack through the first to the fourth grade are appropriate to the needs and levels of the students which is also consistent with the findings of this study.…”
Section: Findings and Discussionsupporting
confidence: 90%
“…Al- Barakat et al (2006) examined the compatibility of the first four primary textbooks used in Jordanian public schools. The researchers used a questionnaire and an interview in order to evaluate the contents, layout, evaluation tasks, the teachers' guide for the series, and examined the availability of the supplementary materials.…”
Section: English Textbooks Research On Arabic Speaking Countriesmentioning
confidence: 99%
“…Al-Barakat, Bataineh, Al-Karasneh & Bataineh (2006) evaluated the pedagogical value of the Action Pack Textbook Series (APTS) taught in the first four primary stage classes in Jordanian public schools as perceived by (300) teachers using an evaluation checklist and a semi-structured interview. They found that poor ratings were minimal, and that APTS is adaptable to both teachers' and pupils' needs, provides a broad range of resources that can be selectively integrated into the curriculum, has interesting, engaging and effective instructional materials, has a flexible, versatile and easy to follow Teacher Book, has appropriate non-text materials for promoting learning, and has students' materials which are well written, age-appropriate and compelling in content.…”
Section: Review Of Related Literaturementioning
confidence: 99%
“…To achieve the aim of the study, which is to evaluate the pedagogical value of UAE English Skills from supervisors' and teachers' perspectives, the authors adopted a slightly modified version of Al- Barakat et al (2006) evaluation checklist. The rationale for using Al-Barakat et al's checklist is two-fold: (1) theirs is one of the most recent studies on the topic, and (2) their checklist was designed to evaluate a Jordanian series which is bound to hold uncanny similarities to one used in the UAE.…”
Section: Subjects Instrumentation and Data Collection And Analysismentioning
confidence: 99%